Development of Legal Regulation of Arctic Marine Oil and Gas Resources: Soft-law Approach - I. V. Panichkin (Московский журнал международного права, 2011)
In recent years there has been seen rapid growth of interest in the Arctic marine oil and gas, which supposedly constitute 30-40 % of the world’s undiscovered oil and gas resources. At the same time, accidents, which could take place while developing of the resources, can not only cause irreparable injury to the Arctic ecosystem, but have global consequences. This article analyzes current international law regulating the development of the Arctic marine oil and gas resources and examines one of the directions of its development ‒ cooperation amount the Arctic States in international organizations and forums, creating “soft-law” rules. The article also considers to acts of international non-governmental organizations (unions, associations and etc.). In conclusion, the article analyzes the advantages and disadvantages of using of the “soft-law approach” to regulate the development of the Arctic marine oil and gas resources.